AB0485 INVESTIGATION OF PERMANENT ORGAN DAMAGE IN GIANT CELL ARTERITIS: DISEASE FLARES ARE ASSOCIATED WITH INCREASED DAMAGE SCORES. (2nd June 2020) - Ince, B.; Artan, S.; Yalçinkaya, Y.; Artim-Esen, B.; Gül, A.; Ocal, M. L.; Inanc, M.
Abstract : Background: Development of organ damage is a major concern in patients with systemic vasculitis. Treatment may also contribute to this important outcome. Scoring systems has been developed to evaluate organ damage in systemic vasculitis and specifically for large vessel vasculitis (1). Objectives: We aimed to investigate permanent organ damage and determining factors in our giant cell arteritis GCA cohort. Methods: Organ damage detected at the time of diagnosis and / or follow-up and irreversible for at least 3 months in GCA patients followed up between 1998-2018 were recorded by using Vasculitis Damage Index (VDI) and Vascular Vasculitis Damage Index (LVVID) fom patient records of our vasculitis clinic. In the statistical evaluation, chi-square, students t-test and logistic regression analysis were used. Results: Eighty-nine patients (64% women, mean age 67.9 ± 9.1) included in the study, the mean follow-up duration was 61.6 ± 58.6 months. All organ damage findings according to both VDI and LVVID are shown in table-1. In this cohort, cardiovascular damage items and diabetes mellitus were prevalent at baseline. At least one damage item was present in 53 (59, 5%) according to VDI; 54 (%60, 7) according to LVVID and agreement was high between two damage indices (kappa=0.97). Forty-seven of patients (52%) had a damage item presumably with contribution of GC treatment e.g. locomotor system findings, hypertension, diabetes and cataract; 12 (13, 5%) had damage items related to disease (total or partial vision loss, ischemic optical neuropathy). Mean time to diagnosis after initial symptoms was longer in patients with permanent vision loss (10, 2±4, 3 vs. 5, 2±1, 2 months p=0.006). The presence of damage was associated with flares in univariate and multivariate analysis (29/54 vs. 2/35 p<0, 001 OR=19 %95 GA 4, 2– 87, 9). All patients who had a flare during the first year (n = 15) developed signs of damage at follow-up. No association was found between the development of organ damage and the age of diagnosis, the time between first complaint and diagnosis, presence of cranial, ophthalmologic findings, PET-CT positivity, cumulative steroid dose, and DMARD use. Conclusion: In our study, permanent organ damage was analysed by using diffrerent indices. In this patient population baseline cardiovascular damage and diabetes mellitus were frequent as expected but information for osteoporosis was lacking. More than half of the patients had damage and significant part of the present items was considered due to corticosteroid treatment. The most common damage item developed was osteoporosis. There was a very good agreement between the two indices, despite few specific items in LVVID. The striking relationship of disease flare with damage and frequency of visual problems despite treatment indicate the necessity of new treatment strategies. References: [1]Kermani, T.A., et al., Evaluation of damage in giant cell arteritis. Rheumatology (Oxford), 2018. 57 (2): p. 322-328. Disclosure of Interests: None declared